Makna Semantik dan Simbolisme dalam Teks Agama Buddha: Kajian Hermeneutik terhadap Konsep Dukkha dalam Dhammacakkappavattana Sutta - Dody Dody; Hesti Sadtyadi (Jurnal Budi Pekerti Agama Buddha, 2024)
This study explores the semantic dimensions and symbolic meanings found in Buddhist religious texts by applying a hermeneutic analysis to the concept of dukkha in the Dhammacakkappavattana Sutta. Commonly translated as suffering, dukkha carries broader existential implications, such as dissatisfaction, impermanence, and the inherent unsatisfactory nature of existence. Employing a qualitative hermeneutic approach combined with semantic and semiotic analysis, the research identifies three interconnected layers of meaning within dukkha: the literal level, referring to physical and mental suffering; the contextual level, which reflects the human existential condition; and the spiritual level, where dukkha becomes a gateway toward liberation. The results indicate that a nuanced understanding of the semantic richness of dukkha is crucial for a deeper comprehension of the Four Noble Truths as the core framework of Buddhist doctrine. This study contributes to interdisciplinary discourse among linguistics, religious studies, and Buddhist practice, emphasizing that sacred language functions not only to convey doctrine but also to encourage inner reflection and spiritual transformation.